THE DIAMOND BRIDGE - Addressing transport poverty in Reykjanes - Oddur Gunnarsson Bauer 1990- (2023)
Dependency on the car is a vital piece of the social fabric in Iceland. This has resulted in large groups of people being in a compromised position due to bad planning decisions that use the personal car their cornerstone. Additionally, over dependency on travel via personal car is something that is unsustainable in the long run, both due to the large amounts of fossil fuels that is required for it‘s continued use on top of the societal problems. This thesis project proposes a solution to both issues via a singular architectural response within the municipality of Reykjanes in Iceland. It is an airport town, and a suburb of sorts to the nearby capitol Reykjavík. This makes the town very susceptible to the effects of transport poverty. The solution is proposed as a refurbishment of sorts, with existing plans and situations in the region altered in a way that counters the negative effects of transport poverty in Reykjanes by way of greener modes of travel.